25 Jahre Deutsche Einheit: eine Erfolgsgeschichte? - Joachim Ragnitz; Gerhard Heimpold; Jens Hölscher; Rainer Land; Klaus Schroeder (Wirtschaftsdienst, 2015)
Vor 25 Jahren trat die Währungs-, Wirtschafts- und Sozialunion zwischen der Bundesrepublik und der damaligen DDR in Kraft. Direkt nach der Wende 1990 hatte Ostdeutschland ökonomisch rasch aufgeholt. Unterschiede in der Wirtschaftskraft zwischen Ost und West bleiben jedoch bis heute bestehen, obwohl weiterhin erhebliche Transfers nach Ostdeutschland fließen. Diese Unterschiede lassen sich unter anderem durch die Wirtschaftsstruktur und die Transformationshistorie begründen, sie sind aber auch sozioökonomisch und politisch verursacht. Ein wesentlicher Aspekt ist dabei, dass die ostdeutschen Länder den westdeutschen Entwicklungspfad übernommen haben, was einen Aufholprozess immer schwieriger werden lässt. – – Twenty-five years after reunification, economic fundamentals between East Germany and West Germany continue to differ. Massive financial transfers could not close the significant "prosperity gap" between the two former countries, but they did reduce it noticeably. This is most obvious with respect to indicators such as GDP per capita and unemployment. Fast convergence is unlikely to occur, as economic development is strongly driven by technology that might generate economies of scale, thereby favouring regions which are already well developed. Therefore, economic policy should no longer aim at convergence but rather at economic growth. Despite considerable progress, more structural change will be necessary for further convergence. Furthermore, the decades-long division generated fundamental political and psychological differences, which continue to be felt. One important factor in the continued economic disparity between the two is that East Germany has had to follow the West German development path, which only makes the catching up process more difficult.
Keywords: O10; O40; P20; 330; Strukturwandel; Wirtschaftliche Anpassung; Öffentliche Meinung; Wirtschaftsordnung; Sozialstaat; Deutschland